The Olfactory Organ Is a Unique Site for Neutrophils in the Brain - Palominos, M. Fernanda; Calfún, Cristian; Nardocci, Gino; Candia, Danissa; Torres-Paz, Jorge; Whitlock, Kathleen E. (Frontiers in Immunology, 2022)
In the vertebrate olfactory tract new neurons are continuously produced throughout life. It is widely believed that neurogenesis contributes to learning and memory and can be regulated by immune signaling molecules. Proteins originally identified in the immune system have subsequently been localized to the developing and adult nervous system. Previously, we have shown that olfactory imprinting, a specific type of long-term memory, is correlated with a transcriptional response in the olfactory organs that include up-regulation of genes associated with the immune system. To better understand the immune architecture of the olfactory organs we made use of cell-specific fluorescent reporter lines in dissected, intact adult brains of zebrafish to examine the association of the olfactory sensory neurons with neutrophils and blood-lymphatic vasculature. Surprisingly, the olfactory organs contained the only neutrophil populations observed in the brain; these neutrophils were localized in the neural epithelia and were associated with the extensive blood vasculature of the olfactory organs. Damage to the olfactory epithelia resulted in a rapid increase of neutrophils both within the olfactory organs as well as the central nervous system. Analysis of cell division during and after damage showed an increase in BrdU labeling in the neural epithelia and a subset of the neutrophils. Our results reveal a unique population of neutrophils in the olfactory organs that are associated with both the olfactory epithelia and the lymphatic vasculature suggesting a dual olfactory-immune function for this unique sensory system.